2020
DOI: 10.1002/adfm.202002369
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Oxygen Storage Nanosystem for Near‐Infrared Light‐Triggered Oxygen Supplies to Antagonize Hypoxia‐Induced Therapeutic Resistance in Nasopharyngeal Carcinoma

Abstract: O2‐delivering nanosystems have been used to antagonize hypoxia‐induced tumor therapeutic resistance. However, short‐time oxygen storage is still a bottleneck for these O2‐delivering nanosystems, which results in a decrease in blood circulation time and accumulation of oxygen in tumors, thus reducing the tumor therapeutic efficacy. Herein, a long‐term oxygen storage nanosystem (O2‐PIr@Si@PDA) is designed to overcome hypoxia for the treatment of nasopharyngeal carcinoma. This nanosystem is constructed by using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…[ 1 ] Numerous studies have shown that tumor hypoxia can induce cell cycle arrest, increase protein resistance, and increase expression of DNA repair enzymes in cancer cells, resulting in drug resistance and invalidated treatment. [ 2 ] Therefore, tumor hypoxia is a major cause of failure in the treatment of solid tumors in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Numerous studies have shown that tumor hypoxia can induce cell cycle arrest, increase protein resistance, and increase expression of DNA repair enzymes in cancer cells, resulting in drug resistance and invalidated treatment. [ 2 ] Therefore, tumor hypoxia is a major cause of failure in the treatment of solid tumors in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many potential and opportunities, challenges in their development or clinical translation still exist and require good resolution: 1)Biosafety of nanomaterials in the body is vital to its biological application. [ 168,169 ] Thus, when looking forward to the development of new nanomaterials, the following strategies may be beneficial to ameliorate their biosafety, namely i) Nanomaterials with targeting activities to radiation‐damaged organ can be designed or the nanomaterials can be injected into the organ; ii) Nanomaterial with a relatively long residence time in the radiation‐injured organ can be designed to fully exert the function of the drug. Thereafter, the nanomaterial should degrade or be excreted from the body as soon as possible; and iii) As mentioned above, the strategy of nanolization of natural food radioprotectors can be widely applied because the natural food composite has a lower biosafety risk to the body as compared to many inorganic or organic synthetic nanomaterials. 2)The pathogenesis/injury mechanisms of various diseases, which is one of the most important guidelines for drug design, should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Most tumors have more severe hypoxia levels than normal tissues and hypoxia often occurs in the center of solid tumors, which is a negative prognostic and predictive factor due to multiple effects caused by hypoxia, such as chemotherapy resistance, angiogenesis, invasion, metastasis, radiotherapy resistance and metabolic change [32] . Given its central role in tumor progression and therapeutic resistance, tumor hypoxia is considered as a useful untapped target in cancer treatment [33, 34] . For example, pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer, which has a 5‐year survival rate of ca.…”
Section: Figurementioning
confidence: 99%
“…[32] Given its central role in tumor progression and therapeutic resistance, tumor hypoxia is considered as a useful untapped target in cancer treatment. [33,34] For example, pancreatic ductal adenocarcinoma (PDAC) is the most common type of pancreatic cancer, which has a 5-year survival rate of ca. 7 % and a very poor prognosis.…”
Section: Angewandte Chemiementioning
confidence: 99%